Indoleamine 2,3-dioxygenase 1 signaling orchestrates immune tolerance in Echinococcus multilocularis-infected mice - Meng, Ru; Fu, Yong; Zhang, Yaogang; Mou, Yalin; Liu, Gongguan; Fan, Haining (Frontiers in Immunology, 2022)
The cestode Echinococcus multilocularis infection causes lethal zoonotic alveolar echinococcosis (AE), a disease rendering severe damage to the public health worldwide. The persistent hepatic tumor-like disease in AE patients has been largely attributed to aberrant T cell responses, of which Th1 responses are impeded, whilst Th2 and regulatory T cell responses are elevated, creating an immune tolerogenic microenvironment in the liver. However, the immune tolerance mechanisms need further investigation. Dendritic cells (DCs) are key cellular components in facilitating immune tolerance in chronic diseases, including AE. Here, we demonstrate that indoleamine 2,3-dioxygenase 1-deficient (IDO1-/-) mice display less severe AE as compared to wild-type (WT) mice during Echinococcus multilocularis infection. Mechanistically, IDO1 prevents optimal T cells responses by programming DCs to a tolerogenic state. Specifically, IDO1 prevents the maturation and migration potential of DCs, as shown by the significantly enhanced expression of antigen-presenting molecule (MHC II), costimulatory molecules (CD80 and CD86), and chemokine receptors (CXCR4 and CCR7) in infected IDO1-/- mice as compared to infected wild-type mice. More importantly, the tolerogenic phenotype of DCs is partly reverted in IDO1-/- mice, as indicated by enhanced activation, proliferation, and differentiation of both CD4+ and CD8+ - T cells upon infection with Echinococcus multilocularis, in comparison with WT mice. Interestingly, in absence of IDO1, CD4+ T cells are prone to differentiate to effector memory cells (CD44+CD62L-); in contrast, CD8+ T cells are highly biased to the central memory phenotype (CD44+CD62L+). Overall, these data are the first to demonstrate the essential role of IDO1 signaling in inducing immunosuppression in mice infected with Echinococcus multilocularis, which might be helpful to develop a novel therapeutic target for AE.